Analysis of the Motion Response on the Cylindrical Platform of the Deep Sea - Achmad Baidowi; Irfan Syarif Arief; Ahmadi Munib (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2019)
The strategic point of potential tidal energy in Indonesia can be a solution to the energy crisis, and as the development of renewable energy. Several concepts of the floating marine current turbine (MCT) have been offered, one of them is the cylindrical platform. The object of the conducted study is 33 m cylindrical platform with twin horizontal axis MCT installed underneath the platform. The analysis begins with the platform properties which include Centre of gravity, gyration radius and inertial. The environmental loads are 1 m/s and 2 m/s current speed, 2.4 m wave height, and 22 knots wind. The properties will be used as input for motion analysis and mooring line tension. The results of the analysis with turret configuration of three lines and four lines show that the response amplitude operator (RAO) on the largest translational motion on surge motion as far as 4 m and rotational motion of 4.5 degrees. For the analysis of the mooring system the average maximum tension of the mooring chain reaches 2000 kN, with the maximum proof load at the value of 2245.82 kN which resulted to a safety factor of 1,73 and it still complies to API RP 2SK Standard.